COMMUNICATIVE LANGUAGE TEACHING AND ITS IMPACT ON YOUNG LEARNERS' SPEAKING COMPETENCE - Musoyeva Aziza Botirovna,; Fozilova Dildora Oybek qizi, (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: Through systematic analysis of existing pedagogical frameworks and empirical literature, this research investigates how CLT principles—authenticity, meaningful interaction, learner-centeredness, and task-based activities—contribute to oral proficiency development in early language education. The methodology employed a comprehensive theoretical analysis of CLT implementations across diverse educational contexts, focusing on the relationship between communicative approaches and speaking skill acquisition. Findings reveal that CLT significantly enhances young learners' speaking competence by fostering natural language use, reducing affective barriers, and promoting interactive communication patterns. The results demonstrate that CLT's emphasis on meaningful communication over grammatical accuracy creates supportive environments where young learners develop fluency, confidence, and pragmatic competence. This study concludes that CLT represents an effective pedagogical approach for cultivating speaking abilities in young language learners when appropriately adapted to developmental stages and cultural contexts.